Implementation of Agile Methods on Development of Savings and Loan Cooperative Information Systems - Robi Setiawan; Irman Effendy (Journal of Information System and Informatics, 2022)
Koperasi Sehati Makmur Abadi is a savings and loans cooperative whose data processing process still uses a system that is accessed through an old version of the browser and if the browser is updated to the latest version, it will result in the system not being able to run. The system used now sometimes experiences errors because it still uses old technology, it is certain that if it still uses old technology, it will make the business will be left behind with the times that continue to develop, and in the old system the appearance of the system is not attractive Anda lso the system used does not involve its members, in the development of technology which now the system has involved many users as in banks have given access to their customers so that they can check balances, transfer transactions and so on. This problem must be resolved so that the business can develop and not be left behind by other competitors. Using a web-based information system application can make it easier if you want to open it in various browsers or devices such as gadgets and can be used anywhere and anytime. The use of methods in this research starts from the type of data used is primary data or single data that researchers get through interviews, direct observations, and literature studies, while in the use of the system design method using agile methods and the implementation in this research uses PHP language for website development and for the database itself using databases MySQL. From the results of this research or research, it is hoped that the system created can process data such as member data, installments, loans, deposits and so on, it is hoped that it can facilitate the Sehati Makmur Abadi cooperative in managing data